A multinational study of self‐compassion and human immunodeficiency virus‐related anxiety. (2nd September 2013) - Kemppainen, J.; Johnson, M.O.; Phillips, J.C.; Sullivan, K.M.; Corless, I.B.; Reid, P.; Iipinge, S.; Chaiphibalsarisdi, P.; Sefcik, E.; Chen, W.‐T.; Kirksey, K.; Voss, J.; et al.
<x xml:space="preserve">Abstract</x> Aim This study represents an initial effort at examining the association between the construct of self‐compassion and human immunodeficiency virus (HIV)‐related anxiety in a multinational population with HIV disease. Background Previous studies have found that self‐compassion is a powerful predictor of mental health, demonstrating positive and consistent linkages with various measures of affect, psychopathology and well‐being, including anxiety. Methods Cross‐sectional data from a multinational study conducted by the members of the International Nursing Network for HIV Research (n = 1986) were used. The diverse sample included participants from Canada, China, Namibia, the United States of America and the territory of Puerto Rico. Study measures included the anxiety subscale of the Symptom Checklist‐90 instrument, the Brief Version Self‐Compassion Inventory and a single item on anxiety from the Revised Sign and Symptom Checklist. Findings Study findings show that anxiety was significantly and inversely related to self‐compassion across participants in all countries. We examined gender differences in self‐compassion and anxiety, controlling for country. Levels of anxiety remained significantly and inversely related to self‐compassion for both males (P = 0.000) and females (P = 0.000). Levels of self‐compassion and anxiety varied across countries. Conclusions Self‐compassion is a robust construct with cross‐cultural relevance. A culturally based brief treatment approach aimed at increasing self‐compassion may lend itself to the development of a cost effective adjunct treatment in HIV disease, including the management of anxiety symptoms.